Weight of the Human Kidney A Study on 70 Autopsy Cases (Delta Medical College Journal, 2016)
Background: Variations in weight of the kidney in different populations and in different age groups are evident.Objective: The aim of the present study was to find out age related changes in weight of the kidney in a Bangladeshi population and compare with previous local and foreign studies.Materials and method: This cross-sectional study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, Bangladesh from July 2008 to June 2009, based on collection of 140 post mortem human kidneys collected from 70 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine of same institute. All the samples were divided into three different age groups - A (10-19 years), B (20-39 years) and C (40-59 years), and the weight of each kidney was measured by using a digital balance and recorded.Results: The weight of the right and left kidneys were found 86.18±0.32 gm and 86.10±0.10 gm in group A, 102.25±7.64 gm and 101.96±7.27 gm in group B, 95.59±0.75 gm and 95.19±1.24 gm in group C respectively. No difference was found between the right and left kidneys in any group. However, statistically significant differences were evident among age groups.Conclusion: The weight of the kidney was found to increase up to 4th decade of life and then declined with further advancing age.Delta Med Col J. Jan 2016 4(1): 31-34